Mormons in America - Bushman, Claudia L.; Bushman, Richard L. (New York : Oxford University Press, 1952)
Chronicles the history of the Church of Jesus Christ of Latter-Day Saints beginning in America in the early 1800s and continuing to the present day throughout the world.
Includes bibliographical references (p. 136-137) and index.
Keywords: Church of Jesus Christ of Latter-day Saints -- Juvenile literature; Church of Jesus Christ of Latter-day Saints; Latter Day Saint churches -- United States -- Juvenile literature; Latter Day Saint churches